Transmisi dan Orientasi Nilai Budaya Kerja Pegawai Pemerintah - Johar Permana (Universitas Riau, 2010)
Although a transitional change of improving good services in organizational culture isslowly changing, the value transmission in Indonesia civil servants setting is very important to beunderstood optimistically. That is a self-adjustment of the employees working in a natural andpositive ways. But, how the value transmission of quality-oriented work culture occurs among ofthem? This study shows the description of the transmission of cultural values by working in aninterpretive analysis based on the Hawley’s knowledge (2001: 76-78) describing the gradationvalue of an organization has not grown into a thriving organization. Through a qualitative study,working with a leader on the top, ten employees in the middle, and fourteen employees at the lineas a participant observer (education consultant) for 2005 and 2006 at one of education offices inWest Java, this study concludes that the transmission of cultural values as well as an organizationalculture change requires understanding the noble values, especially comitments on the top level,dynamics in the middle, and loyalty at the line.